Social proximity and misinformation: Experimental evidence from a mobile phone-based campaign in India - Alex Armand; Britta Augsburg; Antonella Bancalari; Kalyan Kumar Kameshwara (Institute for Fiscal Studies (IFS), 2022)
We study how social proximity between the sender and the receiver of information shapes the effectiveness of preventive health behaviour campaigns and the persistence of misinformation. We implement a field experiment among a representative sample of slum residents in two major Indian cities characterized by Hindu-Muslim tensions. We show that informative messages are effective at improving evidence-based behavior, but not non-evidence-based behavior. These findings do not differ by social proximity, signalled by religion. However, when sender and receiver share the same religion, the intervention significantly reduces misinformation carrying in-group salience, highlighting the role of social proximity in fighting misinformation.
Keywords: C93; D91; I12; I15; O12; 330; Misinformation; Religion; Identity; Social proximity; India; Social media; COVID-19; randomized field experiment